The country that does not fit. Policies of citizen access to public audiovisual systems in South America - Monje, Daniela Inés (2016)
This article proposes a comparative reading on the changes in media systems that were conducted in seven countries in South America in the last decade which makes possible a creation or re-emergency of state or public media. In seeking to identify traits of a Latin American model of public media, we were particularly interested in analysing public access policies that every national system proposes as a way for greater plurality of voices and increased participation modes. We work considering three variables: funding, content and control of the media by citizens. Results show a scrappy process and that despite progress in some areas, there is a strong state dependence of public media and public access are not fully exercised.